Types and Function of Taboo Words Found in American Gangster Movie - I Komang Sulatra; I Dewa Ayu Devi Maharani Santika; Dafrosa Resiana Serti (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
This study aims at (1) finding out the types of taboo utterances found in American Gangster movie, and (2) analysing the function of taboo utterances found in American Gangster movie. The data of this study were taken from a movie entitled American Gangster. The genre of this movie is crime drama. This study used descriptive qualitative method, by describing the word or phrase of taboo words from the movie. The qualitative method is applied in order to give clear analysis on the data according to the theory proposed by Battistella (2005) and Wardhaugh (2006). The result of this study shows that all types and functions of taboo words were found. First, there are four types of taboo words are epithets, profanity, vulgarity, obscenity. Vulgarity is the most dominant type used by the characters in the movie. Second, there are four functions of taboo words, such as; to draw attention to oneself, to show contempt, to be provocative, to mock authority. The most function of taboo words found in the movie is to show contempt. It is employed by characters in the movie. To support the analysis were used some dictionaries of taboo words. The phenomenon that usually happens in our life which nowadays many people used taboo words in their daily communication and it is one of the most efficient ways to expressing feeling in any situation.